PARENTING STYLES AS PREDICTOR OF CYBER VICTIMIZATION AND ANXIETY DISORDERS IN ADOLESCENTS - Mehreen Nisar (International Journal of Contemporary Issues in Social Sciences, 2024)
Present study was conducted to study the relationship of parenting styles (Parental control, parental response,) with cyber-victimization and anxiety disorders (social anxiety disorder, Panic Disorder, Separation Anxiety Disorder, Selective Mutism and Generalized Anxiety Disorder) with the sample of 300 adolescents (age range= 17 to 19), 131 were girls and 169 were boys. In current study Scale of Parenting styles, Florence cyber- bullying-cyber-victimization scales (FCBVSs) and Youth Anxiety Measure for DSM-5, Part I (YAM-5-1) was used. Participants were asked to provide appropriate responses. Psychometric properties of scales were established on sample of current study. All the instruments used in present study found to have satisfactory inter-consistency and satisfactory reliability coefficients of scales as well. Multiple regression analysis was performed that shows parental control negatively predicts the Cyber victimization while parental control positively predicts Anxiety Disorders specifically Separation Anxiety Disorder, Panic Disorder and Generalized Anxiety Disorder. The findings of current research indicates that Parental response negatively predicts anxiety disorders specifically GAD. Results finding also shed light on the fact that permissive parenting makes children more vulnerable for being a Cyber Victim.